Sinergitas Majelis Taklim Ar-Rahmah dalam Meningkatkan Nilai Aswaja An-Nahdliyah Masyarakat Desa Sukosono - Mohammad Ilham; Alex Yusron Al Mufti (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The lack of access to religious education based on Aswaja An Nahdliyah causes a lack of understanding of the jurisprudence of worship and moderate creeds, low interest of the younger generation in Islamic knowledge and the development of rigid religious understanding, which is a problem for the people of Sukosono village. Under these conditions, society needs a place for religious education that can provide an understanding of Islam that is moderate, tolerant and in line with the values ​​of Aswaja An Nahdliyah. The Ar-Rahmah Taklim Council acts as a center for moderate Islamic education through yasinan activities, fiqh studies, dhikr fida', manaqib selapan, and birthday of barzanji. Apart from fostering spirituality, this assembly instills Aswaja values ​​to build a harmonious social life. The aim of this research is to explore the synergy between the Ar-Rahmah Taklim Council and the Sukosono Village community in improving Aswaja values, as well as exploring the resulting positive impact on the social and spiritual life of the community. Qualitative methods were used in this research, involving observation and in-depth interviews at the Taklim Ar-Rahmah assembly. Data was collected through interviews, observation and documentation studies. The results of the research show that the Ar-Rahmah Taklim Council is able to provide benefits to the people of Sukosono Village by increasing moderate understanding of religion, strengthening Islamic brotherhood, becoming a learning forum for the younger generation, preventing the entry of radical ideas, and encouraging women's participation in Islamic education and religious activities.